HUBUNGAN POLA ASUH PEMBERIAN MAKAN DENGAN KEJADIAN STUNTING PADA BALITA DI UPT PUSKESMAS BAHOROK KABUPATEN LANGKAT TAHUN 2021 - Nila Hayati; Mestika Rija Helty (Jurnal Maternitas Kebidanan, 2022)
Stunting is a chronic malnutrition problem caused by an inadequate nutritional intake for a long time due to a feeding that is not by nutritional needs. One of the causes of stunting are feeding a parenting. This study aims to find out about the Relationship between Feeding Parenting Patterns with Stunting the incidence in Toddlers at UPT Bahorok Health Center, Langkat Regency in 2021. This research is descriptive correlation research with the cross-sectional approach. This research has been carried out from September 13, 2021, to September 25, 2021. The population is 716 children under five. Sampling using purposive sampling with a sample of 30 people. The results of the study showed that the majority of the Parenting Feeding Patterns at the Bahorok Health Center, Langkat Regency in 2021, and the majority of stunting in toddlers at the Bahorok Health Center, Langkat Regency in 2021 were very short: < -3.0 SD to <-2, 0 SD. Based on the results of the chi-square test, it was found that the p-value = 0.001 <0.05. So it can be concluded that there is a relationship between feeding parenting and stunting in toddlers at UPT Puskesmas Bahorok, Langkat Regency in 2021. Suggestions in this study are UPT Puskesmas Bahorok, Langkat Regency actively pay more attention to children by taking a persuasive approach to mothers by providing information about nutrition to pregnant women to toddlers to avoid stunting.